Dynamic characteristics of a semi-active fractional-order inerter-based suspension with acceleration-velocity switch control - Yong Wang; Jiachen Li; Mingzhu Ji; Xiwen Qiao; Yang Wang (Journal of Low Frequency Noise, Vibration and Active Control)
The fractional-order differential theory is applied in the hydraulic inerter to describe its mechanical characteristic, a semi-active fractional-order (SA-FO) inerter based on the hydraulic inerter is proposed and used in the vehicle suspension to constitute the semi-active fractional-order inerter-based (SA-FOIB) suspension, which consists of two adjustable inertances. According to the mechanical characteristic of the inerter, the acceleration-velocity switch (AVS) control strategy is proposed to adjust the inertance of the SA-FO inerter. The dynamic model of the SA-FOIB suspension with AVS control is established, its dynamic response under road harmonic excitation is obtained using the averaging method, the dynamic performance under road harmonic and random excitations is analyzed and evaluated by the vehicle body acceleration, suspension dynamic deflection and wheel dynamic load, the optimized structural parameters are obtained using the genetic algorithm optimization method. The results show that for road harmonic excitation, the SA-FOIB suspension can further enhance the high-frequency dynamic performance of the passive fractional-order inerter-based (P-FOIB) suspension, which the high-frequency resonance peaks of the dynamic performance indices are smaller. For road random excitation, the SA-FOIB suspension can decrease the root-mean-square (RMS) values of the suspension dynamic deflection and wheel dynamic load compared with the P-FOIB suspension, while increases the RMS value of the vehicle body acceleration. The optimized SA-FOIB suspension further improves the dynamic performance of the suspension dynamic deflection and wheel dynamic load, which the corresponding RMS values are smaller than the unoptimized SA-FOIB suspension, while deteriorates the vehicle body acceleration.